Analysis of Digital Transformation and Information Democratization for the Community Information Community (KIM) of Musi Banyuasin Regency (Muba), South Sumatra (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
The era of the information society has brought significant changes in the distribution and utilization of information, creating opportunities as well as challenges, especially in supporting the democratization of information. In South Sumatra, the Community Information Community (KIM) has a strategic role in managing and disseminating information to empower the community creatively and independently. However, digital transformation presents new dynamics, including the rise of fake news and post-truth culture, which requires KIM to adapt to remain relevant in supporting information democracy. This study explores the role of KIM as a government partner in encouraging public information disclosure amid challenges such as the digital divide and low technological literacy. The adoption of digital technology is expected to strengthen KIM's capacity to provide fast, precise, and inclusive information. With a holistic approach, this research aims to formulate an empowerment strategy for KIM to maximize its role in supporting an informed, critical, and empowered society in the era of digital transformation.